Accuracy of a computer vision system for estimating biomechanical measures of body function in axial spondyloarthropathy patients and healthy subjects - Cronin, Neil J; Mansoubi, Maedeh; Hannink, Erin; Waller, Benjamin; Dawes, Helen (Clinical rehabilitation, 2023)
Advances in computer vision make it possible to combine low-cost cameras with algorithms, enabling biomechanical measures of body function and rehabilitation programs to be performed anywhere. We evaluated a computer vision system's accuracy and concurrent validity for estimating clinically relevant biomechanical measures. Cross-sectional study. Laboratory. Thirty-one healthy participants and 31 patients with axial spondyloarthropathy. A series of clinical functional tests (including the gold standard Bath Ankylosing Spondylitis Metrology Index tests). Each test was performed twice: the first performance was recorded with a camera, and a computer vision algorithm was used to estimate variables. During the second performance, a clinician measured the same variables manually. Joint angles and inter-limb distances. Clinician measures were compared with computer vision estimates. For all tests, clinician and computer vision estimates were correlated ( values: 0.360-0.768). There were no significant mean differences between methods for shoulder flexion (left: 2 ± 14° (mean ± standard deviation), = 0.99, < 0.33; right: 3 ± 15°, = 1.57, < 0.12), side flexion (left: - 0.5 ± 3.1 cm, = -1.34, = 0.19; right: 0.5 ± 3.4 cm, = 1.05, = 0.30) and lumbar flexion ( - 1.1 ± 8.2 cm, = -1.05, = 0.30). For all other movements, significant differences were observed, but could be corrected using a systematic offset. We present a computer vision approach that estimates distances and angles from clinical movements recorded with a phone or webcam. In the future, this approach could be used to monitor functional capacity and support physical therapy management remotely.